Produktivitas Kerja Karyawan Ditinjau Dari Lingkungan Kerja Dan Tingkat Kesejahteraan Pada Pt. Dan Liris Di Sukoharjo Tahun 2016 - Sofyana, Avit May; , Dr. Sabar Narimo, M.M., M.Pd (2016)
ABSTRACT Avit May Sofyana. A 210 110 150 EMPLOYEE PRODUCTIVITY BASED ON WELFARE WORK ENVIRONMENT AND LEVEL OF PT. DAN LIRIS IN THE YEAR 2016 SUKOHARJO. Thesis. Accounting Education Studies Program Faculty of Teaching and Education University of Muhammadiyah Surakarta. April, 2016. The purpose of this study was to determine: 1). The influence of the working environment on the productivity of employees at PT. Dan Liris in Sukoharjo 2016. 2). The influence of the level of welfare to work productivity of employees at PT. Dan Liris in Sukoharjo 2016. 3). The influence of the working environment and the welfare of the productivity of employees at PT. Dan Liris in Sukoharjo 2016. This research includes associative quantitative research whose conclusions obtained based on the results of statistical analysis. This study took place PT. Dan Liris. Population 150 employees, 105 employees of samples, sampling using proportionate random sampling technique. Data collection techniques by using documents and questionnaires that have been tested with normality test, reliability test and test multikolinieritas. The analysis technique used is multiple regression. Results of regression analysis regression equation; Y = 17,953+ 0,288X1 + 0,194X2, which means that the productivity of employees affected by the work environment and the level of welfare, based on the analysis and discussion can be concluded that: 1). Work environment positive effect on employee productivity, it is based on the results of multiple linear regression analysis (t test) is known thitung> ttable, namely 4.222> 1.984 and the significance value <0.05, namely 0.000. 2). Well-being is a positive effect on employee productivity, it is based on the results of multiple linear regression analysis (t test) is known thitung> ttable, namely 2.631> 1.984 and the significance value <0.05, ie 0,010. 3). The working environment and welfare together a positive effect on employee productivity, it is based on the results of multiple linear regression analysis (F test) is known Fhitung> Ftable is 17.270> 3.07 with a significance value <0.05 is 0.000. Work environment variables contribute effectively 17.0%. Variable levels of well-being contribute effectively 8.3%. So that the total contribution of both of 25.3% while 74.7% are influenced by other variables not examined by researcher. Keywords: productivity of employees, work environment, welfare